Commodification of Development Programming on Radio in Northern Ghana. Issue 2 (3rd April 2018) - Alhassan, Amin; Odartey-Wellington, Felix; Faisal, Amadu Mohammed
ABSTRACT: This article discusses the commodification of development programming such as news and other content in the Ghanaian media space. It uses the case of two NGOs operating in the Northern Region to examine how development programming is transmitted via FM radio stations in the region. Using in-depth interviews and observations as methodologies, the study investigates the evolving phenomenon of development NGOs buying airtime to broadcast development messages and also examines how this monetisation of development content dissemination impacts the practice of journalism as a civic act. The irony of NGOs as actors in the gift economy becoming agents of commodification of development content brings into focus the political and economic dimensions of the intersection of market and non-market relations in development practice. We argue that this trend of development programme dissemination displaces the civic responsibility of the media who are supposed to inform and educate the listening community through journalism. The article recommends policy evolution to realign the scope and focus of local media with development reporting.